Impact of Obesity on the Rate of Recurrent Spontaneous Preterm Birth in Women Treated with 17-alpha Hydroxyprogesterone Caproate - Hauspurg, Alisse; Lemon, Lara S.; Serra, Allison E.; Sharma, Shringi; Venkataramanan, Raman; Caritis, Steve N. (American Journal of Perinatology, 2018)
Objective We sought to determine if the rate of recurrent spontaneous preterm birth (PTB) in women treated with 17-α hydroxyprogesterone caproate (17-OHPC) is modified by maternal body mass index (BMI).Study Design We performed a secondary analysis of the Maternal-Fetal Medicine Units Network omega-3 fatty acid supplementation to prevent recurrent PTB randomized controlled trial. All women received 17-OHPC.Results A total of 708 women were included. Rates of spontaneous PTB did not vary significantly by BMI category. With stratification by obesity class and gestational age at delivery, the unadjusted risk for PTB using earlier gestational cutoffs (< 35, 32, and 28 weeks) demonstrated an association between preterm delivery and increasing severity of obesity. With adjustment for potential confounders, there was no statistically significant relationship between BMI and spontaneous PTB.Conclusion We demonstrated that the risk of PTB in women receiving 250 mg 17-OHPC is not dependent on maternal BMI after adjustment for confounding variables. Pharmacokinetic studies have demonstrated a wide variation in plasma concentration of 17-OHPC across the population with likely considerable overlap in plasma concentrations among the obese and nonobese population. Further studies are needed to evaluate the impact of BMI on efficacy of 17-OHPC prior to any dose adjustment in this population.
Keywords: 17-α hydroxyprogesterone caproate; BMI; obesity; preterm birth; recurrent preterm birth; spontaneous preterm birth